2017
DOI: 10.1165/rcmb.2016-0161oc
|View full text |Cite
|
Sign up to set email alerts
|

Water Permeability Adjusts Resorption in Lung Epithelia to Increased Apical Surface Liquid Volumes

Abstract: The apical surface liquid (ASL) layer covers the airways and forms a first line of defense against pathogens. Maintenance of ASL volume by airway epithelia is essential for maintaining lung function. The proteolytic activation of epithelial Na channels is believed to be the dominating mechanism to cope with increases in ASL volumes. Alternative mechanisms, in particular increases in epithelial osmotic water permeability (P), have so far been regarded as rather less important. However, most studies mainly addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…However, other studies found that perturbations of aquaporin activity disturb transepithelial water transport and volume homeostasis in the airways [2, 32, 35, 113, 127], suggesting that TJ-independent water transport pathways through aquaporins contribute significantly to fluid transport across the airway epithelium. A more recent study now suggests that both processes occur in a different manner, where basal water transport activity is dominated by a paracellular pathway, whereas a compensatively increased water resorption is predominantly carried by an aquaporin-dependent transcellular pathway [110]. In airway epithelial cells, cldn2 localises in intracellular stores rather than at the TJs [62] and is regulated by TNF-α [86].…”
Section: Caludins Of the Alveolar And Airway Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies found that perturbations of aquaporin activity disturb transepithelial water transport and volume homeostasis in the airways [2, 32, 35, 113, 127], suggesting that TJ-independent water transport pathways through aquaporins contribute significantly to fluid transport across the airway epithelium. A more recent study now suggests that both processes occur in a different manner, where basal water transport activity is dominated by a paracellular pathway, whereas a compensatively increased water resorption is predominantly carried by an aquaporin-dependent transcellular pathway [110]. In airway epithelial cells, cldn2 localises in intracellular stores rather than at the TJs [62] and is regulated by TNF-α [86].…”
Section: Caludins Of the Alveolar And Airway Epitheliummentioning
confidence: 99%
“…Besides barrier function, decreased fluid resorption across the airway epithelium is an additional susceptibility factor for lung injury and respiratory distress syndrome and worsens the clinical outcome in patients [136]. Airway and alveolar epithelia compensates for alveolar oedema formation or elevated apical surface liquid volumes by up-regulating active ion resorption [31, 39, 49, 55, 92, 123] or via increasing transcellular water permeability [110] to facilitate fluid clearance.…”
Section: Tjs and Respiratory Failurementioning
confidence: 99%
“…AQP1 is unequivocally detected in plasma membranes of endothelial cells that form the barrier of blood vessels along the airways as well as within the respiratory and alveolar regions [18, 21, 29, 44, 66, 72, 89, 102, 112]. AQP3 localizes to epithelial and basal cells of the nasal epithelium [58, 72], basal, and epithelial cells of the trachea, bronchi, and bronchioli [58, 72, 90]. Along the conducting and respiratory airways, AQP3 is incorporated into the lateral membranes of epithelial cells [90].…”
Section: Aquaporins In the Lungmentioning
confidence: 99%
“…AQP3 localizes to epithelial and basal cells of the nasal epithelium [58, 72], basal, and epithelial cells of the trachea, bronchi, and bronchioli [58, 72, 90]. Along the conducting and respiratory airways, AQP3 is incorporated into the lateral membranes of epithelial cells [90]. Also, cuboidal alveolar epithelial type II (ATII) cells express AQP3 [58, 90].…”
Section: Aquaporins In the Lungmentioning
confidence: 99%
See 1 more Smart Citation